Embedding and Sustaining a Focus on Function in Specialty Research and Care. Issue 1 (16th October 2020) - Callahan, Kathryn E.; Boustani, Malaz; Ferrante, Lauren; Forman, Daniel E.; Gurwitz, Jerry; High, Kevin P.; McFarland, Frances; Robinson, Thomas; Studenski, Stephanie; Yang, Mia; Schmader, Kenneth E.
Abstract : Function and the independent performance of daily activities are of critical importance to older adults. Although function was once a domain of interest primarily limited to geriatricians, transdisciplinary research has demonstrated its value across the spectrum of medical and surgical care. Nonetheless, integrating a functional perspective into medical and surgical therapeutics has yet to be implemented consistently into clinical practice. This article summarizes the presentations and discussions from a workshop, "Embedding/Sustaining a Focus on Function in Specialty Research and Care, " held on January 31 to February 1, 2019. The third in a series supported by the National Institute on Aging and the John A. Hartford Foundation, the workshop aimed to identify scientific gaps and recommend research strategies to advance the implementation of function in care of older adults. Transdisciplinary leaders discussed implementation of mobility programs and functional assessments, including comprehensive geriatric assessment; integrating cognitive and sensory functional assessments; the role of culture, environment, and community in incorporating function into research; innovative methods to better identify functional limitations, techniques, and interventions to facilitate functional gains; and the role of the health system in fostering integration of function. Workshop participants emphasized the importance of aligning goals and assessments and adopting a team science approach that includes clinicians and frontline staff in the planning, development, testing, and implementation of tools and initiatives. This article summarizes those discussions. Abstract : See related editorial by Ling et al .